Keterampilan Sosial dan Emosional Anak Usia Dini; Analisis Gender - Sitorus, Ahmad Syukri (Generasi Emas, 2023)
Gender differences have an impact on the behavior displayed. Understanding these differences will provide a real understanding of differences in children's behavior based on gender, including children's social and emotional behavior. The research aims to see how children's social and emotional skills are based on the child's gender. The method used is a comparative study that looks at differences in social skills and emotional skills of early childhood based on gender. Data collection used instruments to measure children's social and emotional skills to 45 boys and 32 girls in seven early childhood education units in North Sumatra. Data were analyzed through t-test. The results showed that the average social skills of boys were 28.36 and 29.88 for girls' social skills, and the average emotional skills of boys were 22.18 and 23.56 for girls' emotional skills. This means that descriptively the emotional skills of girls are higher than the emotional skills of boys. The results of the study are clear that girls have higher social skills and emotional skills than boys. This is because girls have emotional expressions that are more neutral, calm and peaceful.